SYNERGY OF COMPETENCES IN AERONAUTICAL ENGLISH EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Successful communication between military pilots and air traffic controllers is vital for ensuring the safety and efficiency of aviation operations. While linguistic competence is fundamental, efficient communication in this context transcends mere language proficiency. The research study explores some contemporary under-researched theoretical and practical issues regarding the acquisition of the military aeronautical English language and establishes a strong correlation between aviation linguistic competence and interactive, cross-cultural and professional competence. This article explores the synergy of these competences and underscores the significance of integrating them in aviation English education. The synergy of competences equips pilots and controllers with the multifaceted skills necessary for ensuring the safety and success of flights in increasingly complex and globalized airspace environments.